Brucellosis in ruminants and pastoralists in Borena, Southern Ethiopia - Edao, Bedaso Mammo; Ameni, Gobena; Assefa, Zerihun; Berg, Stefan; Whatmore, Adrian M.; Wood, James L. N. (PLOS Neglected Tropical Diseases, 2020)
Author summary Brucellosis is a bacterial infectious disease with public health and economic importance mainly in low and middle-income countries (LMICs). The burden of this disease in livestock and its zoonotic importance in humans in sub-Saharan Africa including Ethiopia is poorly understood. In Ethiopia, although epidemiological studies were conducted in intensive dairy herds in high lands areas, there is shortage of data on the epidemiology and public health and impacts of brucellosis. This study was conducted to estimate the prevalence brucellosis in different species of livestock and pastoralists and thereafter to identify the potential risk factors affecting its occurrence and transmission. To this effect, a one health approach was used.